Efficacy and Safety Profile of Different Schedules of Adjuvant Trastuzumab Therapy among Patients with HER2-Positive Breast Cancer: Real-World Experience from a Tertiary Cancer Center in South India - Rajan, Nandini Devi; Menon, Abhilash; Shenoy, Praveen Kumar; Avaronnan, Manuprasad; Shahana, Sherin; Therayangalath, Bindu (South Asian Journal of Cancer, 2024)
One year of adjuvant trastuzumab is the standard of care for HER2-positive breast cancer. In low–middle income countries, delivery of 1-year trastuzumab is challenging due to significant financial burden. Evidence for shorter durations of adjuvant trastuzumab is gaining popularity in this regard. In this study, we compared the effectiveness and safety of 1 year versus shorter durations of adjuvant trastuzumab practiced in our center. In total, 312 patients were included in this analysis. The median age was 52 years. More than two-thirds of patients (67.6%) had stage 2 disease and majority were hormone-receptor-positive (62.5%). The median follow-up duration was 50 months. The 4-year disease-free survival was 97.3%. The 4-year disease-free survival for shorter durations of adjuvant trastuzumab was 98% compared with 96.7% in 1-year trastuzumab therapy group. In univariate analysis, stage at diagnosis was the only factor which had statistically significant association with disease-free survival. In multivariate analysis, none of the variables were found to be predictive of survival. Two patients (0.6%) had significant left ventricular ejection fraction decline.Shorter durations of adjuvant trastuzumab have comparable 4-year disease-free survival to standard 1-year therapy and is an alternative adjuvant treatment option for HER2-positive breast cancer patients in resource-limited settings.
Keywords: HER2-positive breast cancer; adjuvant trastuzumab; shorter durations of adjuvant trastuzumab